Temporal changes in vase water - Salih, Magdi (Cranfield University, 2013)
This study investigated the influence of flower food on vase water quality with the attempt to correlate this with the flowers’ appearance and microbial growth occurring in the vase water. A mixed bouquet of different cut flowers was used in this study for the first time instead of the common practice in the literature of using a single cut flower or a single cultivar. Different combinations of vase solutions; standard water and reverse osmosis water with or without added flower food were used as initial vase solutions and also as the topping up water. The effect of vase solution’s pH on microbial growth and therefore flowers vase quality was also examined. Moreover the analysis of sugar content of vase water was conducted using HPLC and LC/MS. The analysis of vase water in the Cranfield Health laboratory has shown that: Sugar presumably plays a central role in energy for both microbes and plants but the concentration levels present in flower food seems to have no subsequent effect on the growth or otherwise of the microbes even when diluted with top up water. Water uptake by the flowers is little influenced by the presence of flower food or the microbial population. Flower food reduces the pH of Standard water, but not sufficiently enough to inhibit the growth of common pathogens or spoilage organisms. If microbial growth begins, addition of further flower food in the top-up does not inhibit further growth. If reverse osmosis water (ROW) is used with flower food the initial pH is lower than the pH minimum for all common pathogens and the majority of common spoilage organisms. Topping up with ROW with flower food maintains the low pH environment. If growth is initiated due to the presence of microbes capable of growth in the low pH environment, then growth will continue regardless of topping up solution. Microbial growth in ROW with flower food is confined to acidophilic organisms. Addition of weak acid preservatives such as benzoic acid or sorbic acid could control or prevent the growth of such acidophilics, whilst allowing a pH compatible with the flowers to be maintained.
Keywords: Cut flowers; flower food; microbial growth; pH; reverse osmosis water